Factors affecting implementation of digital health interventions for people with psychosis or bipolar disorder, and their family and friends: a systematic review. (March 2019) - Aref-Adib, Golnar; McCloud, Tayla; Ross, Jamie; O'Hanlon, Puffin; Appleton, Victoria; Rowe, Sarah; Murray, Elizabeth; Johnson, Sonia; Lobban, Fiona
Summary: Digital health interventions present an important opportunity to improve health care for people with psychosis or bipolar disorder, but despite their potential, integrating and implementing them into clinical settings has been difficult worldwide. This Review aims to identify factors affecting implementation of digital health interventions for people affected by psychosis or bipolar disorder. We searched seven databases and synthesised data from 26 studies using the Consolidated Framework for Implementation Research. Attitudes and beliefs about interventions were crucial factors for both staff and service users, with negative attitudes and scepticism resulting in a lack of motivation to engage with interventions or complete them. The complexity of the interventions was a barrier for people with psychiatric symptoms, low premorbid intelligence quotient, or minimal information technology skills. The accessibility and adaptability of interventions were key facilitators, but insufficient resources, finances, and staff time were barriers to implementation. Interventions need to be user friendly and adaptable to the needs and capabilities of people with psychosis or bipolar disorder, and the staff who support their implementation. Service users and staff should cofacilitate the process of developing and implementing the interventions.